Pengaruh Kinerja Lingkungan dan Kinerja Keuangan terhadap Nilai Perusahaan : (Studi pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2018-2022) - Siti Amelia; Jon Kenedi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research began with the problem of environmental pollution by manufacturing companies which caused a reduction in clean water supplies, as well as fluctuations in share prices in Basic Industry and Chemical Sector Manufacturing Companies listed on the IDX in 2018-2022, which can result in fluctuating company values so that investors' desire to invest in these companies decreases. This research aimssto measureethe extent to which environmental performance affects company value in the industry and how financial performance affects company value. To analyze the data, descriptive statistical tests and classicallassumption test, in theeform of normalityytest, multicollinearity test, multicollinearity tests, autocorrelation tests and heteroscedasticity tests. Meanwhile, to analyze the data with multipleelinear regression methods.. Theeresearch results show that: 1) financiallperformance variables have annegative and significanteeffect on firmvvalue in this sector; and 2) environmental performance variables have a negative andssignificant effect on firm value in the basic and chemical industry manufacturing sector listed on the Indonesia Stock Exchange from 2018 to 2022.